Direct conversion of untreated cane molasses into butyric acid by engineered Clostridium tyrobutyricum. (April 2020) - Guo, Xiaolong; Fu, Hongxin; Feng, Jun; Hu, Jialei; Wang, Jufang
Highlights: scrA, scrB and scrK were successfully overexpressed in C. tyrobutyricum ATCC 25755. The cane molasses could be utilized efficiently by C. tyrobutyricum ATCC 25755/ scrBAK . The medium composition and initial sugar concentration were optimized. 45.71 g/L butyrate at a yield of 0.39 g/g was obtained in fed-batch fermentation. Abstract: The sucrose metabolic genes ( scrA, scrB and scrK ) from C. acetobutylicum ATCC 824 were successfully overexpressed in C. tyrobutyricum ATCC 25755, endowing it with the ability to co-utilize sucrose, fructose and glucose in the cane molasses. As a result, the engineering strain C. tyrobutyricum ATCC 25755/ scrBAK produced 18.07 g/L and 18.98 g/L butyric acid when sucrose and cane molasses were used as the carbon source, respectively. Furthermore, the medium composition and initial cane molasses concentration were optimized to make full use of the untreated cane molasses. Based on these results, 45.71 g/L butyric acid with a yield of 0.39 g/g was obtained in fed-batch fermentation, and the feedstock cost of using untreated cane molasses was decreased by ~47% when compared with the conventional glucose fermentation. This study demonstrated the potential application of C. tyrobutyricum ATCC 25755/ scrBAK for economic butyric acid production from untreated cane molasses.